THE CRIMINAL ACT OF TRAFFICKING IN HUMANS FOR THE PURPOSE OF EXPLOITATION OF HUMAN ORGANS - Syawal Amry Siregar; Herlina Hanum Harahap; Muhammad Ansori Lubis (Jurnal Ilmiah METADATA, 2026)
The perpetrators of the crime of human organ trafficking are not only criminal syndicates who want to get money through illegal means, but the perpetrators can also be individuals who sell their organs with the intention and goal of getting money. Regulations regarding this crimetrading in organs/body tissue in Law Number 21 of 2007 concerning the Eradication of Human Trafficking which includes trading in body organs as an act of exploitation of people, while in Law Number 36 of 2009 concerning Health it is clearly regulated that human organs are prohibited from being traded under any circumstances.Criminal sanctions against perpetrators of crimesSelling and buying organs/body tissue is expressly stipulated in Article 192 of Law Number 36 of 2009 that anyone who intentionally sells organs or body tissue under any pretext as referred to in Article 64 paragraph (3) shall be punished with a maximum prison sentence of 10 years and a maximum fine of IDR 1 billion.